The world almanac and book of facts, 2012 - Janssen, Sarah , 1982- (New York : World Almanac Books, 2012)
Presents comprehensive facts and statistics on current events, people, and the countries of the world, along with original articles on recent issues and topics ranging from the 2012 presidential candidates to the 2011 World Series and Women's World Cup
1. 2011: special features and year in review -- 2. Economy, business & energy -- 3. Crime -- 4. Military affairs -- 5. Health & vital statistics -- 6. Personalities, arts & media -- 7. Science & technology -- 8. Consumer information -- 9. U.S. facts & history -- 10. World maps & flags -- 11. U.S. government -- 12. U.S. cities, states & population -- 13. World history & culture -- 14. Nations of the world -- 15. Sports
Includes index
New in this edition: 2012 presidential candidates; 2011 World Series and Women's World Cup; The world at a glance; Results of the 2010 census
Keywords: Almanacs, American; Statistics -- Periodicals; United States -- Statistics